An assessment of solar-powered organic Rankine cycle systems for combined heating and power in UK domestic applications. (15th January 2015) - Freeman, James; Hellgardt, Klaus; Markides, Christos N.
Highlights: A domestic-scale combined solar heat and power (CSHP) system is simulated in the UK climate. The CSHP system comprises a solar collector array, an ORC engine and a hot-water cylinder. An exergy analysis, parametric study and annual performance assessment are performed. An average electrical power of 89 W plus an 86% hot water coverage are demonstrated. A total system cost as low as £2700 and a levelised cost electricity of 44 p/kW h are reported. Abstract: Performance calculations are presented for a small-scale combined solar heat and power (CSHP) system based on an Organic Rankine Cycle (ORC), in order to investigate the potential of this technology for the combined provision of heating and power for domestic use in the UK. The system consists of a solar collector array of total area equivalent to that available on the roof of a typical UK home, an ORC engine featuring a generalised positive-displacement expander and a water-cooled condenser, and a hot water storage cylinder. Preheated water from the condenser is sent to the domestic hot water cylinder, which can also receive an indirect heating contribution from the solar collector. Annual simulations of the system are performed. The electrical power output from concentrating parabolic-trough (PTC) and non-concentrating evacuated-tube (ETC) collectors of the same total array area are compared. A parametric analysis and a life-cycle cost analysis are also performed, and the annual performance of the system is evaluated according to the total electrical power output and cost per unit generating capacity. A best-case average electrical power output of 89 W (total of 776 kW h/year) plus a hot water provision capacity equivalent to ∼80% of the total demand are demonstrated, for a whole system capital cost of £2700–£3900. Tracking PTCs are found to be very similar in performance to non-tracking ETCs with an average power output of 89 W (776 kW h/year) vs . 80 W (701 kW h/year).